A decade of intestinal protozoan epidemiology among settled immigrants in Qatar. Issue 1 (December 2016) - Abu-Madi, Marawan; Behnke, Jerzy; Boughattas, Sonia; Al-Thani, Asma; Doiphode, Sanjay
Abstract Background The World Health Organization estimates that about 3.5 billion people worldwide are affected by intestinal parasitic infections. Reports have already emphasized the role of immigrants in outbreaks of parasitic diseases in industrialized countries. With the mass influx of immigrants to Qatar, patent intestinal parasitic infections have been observed. Herein, the prevalence of intestinal protozoan infections was analysed in 29, 286 records of subjects referred for stool examination at the Hamad Medical Corporation over the course of a decade (2005 to 2014, inclusive). Results Overall prevalence of combined protozoan infections was 5.93 % but there were significant temporal trends, age and sex effects and those arising from the region of origin of the subjects. The most common protozoan wasBlastocystis hominis (overall prevalence 3.45 %).Giardia duodenalis, Chilomastix mesnili, Entamoeba coli, Entamoeba hartmanni, Endolimax nana, Iodamoeba butschlii, Entamoeba histolytica/dispar, Cryptosporidium sp. and a single case ofIsospora were also detected. The prevalence of combined protozoan infections, G. duodenalis and the non-pathogenic amoebae all declined significantly across the decade. That ofB. hominis varied between years but showed no directional trend across years and there was no evidence that prevalence ofE. histolyitica/dispar changed significantly. Protozoan infections were observed among all regional groups, but prevalence was higher among subjects from the Arabian Peninsula, Africa and Asia compared to those from the Eastern Mediterranean and Qatar. Prevalence was higher among male subjects in all cases, but age-prevalence profiles differed between the taxa. Conclusion These results offer optimism that prevalence will continue to decline in the years ahead.